Does unemployment invariance hypothesis hold for Canada? - Aysit Tansel; Zeynel Abidin Ozdemir; Emre Aksoy (Koç University-TÜSİAD Economic Research Forum (ERF), 2016)
This article explores the long-run relationship between unemployment rate and labor force participation rate in Canada. The cointegration analysis vindicates the existence of a long-run relationship between these two variables. This finding leads us to doubt the pertinence of the unemployment invariance hypothesis for Canada. This is consistent with the empirical studies for Japan, Sweden and the United States, but contradicts the empirical studies for Australia, Romania and Turkey. There are contradictory studies for the United Kingdom.
Keywords: E24; J64; J21; 330; Unemployment Invariance Hypothesis; Unemployment; Labor Force Participation; Cointegration; Canada